Usia Berpengaruh Dominan Terhadap Perilaku Perawatan Luka Perineum pada Ibu Nifas di RSUD Sleman - Prasetya Lestari (Alma Ata University Press, 2016)
Behavior perineal wound care in postpartum mothers is very important. This is related to prone to the incidence of infection, mothers need to always maintain the cleanliness of the whole body, clothes and cleanliness of their environment. The purpose of this study to determine correlations between age and parity with perineal wound care behaviors among respondents. This study was conducted in January 2016 in Sleman Hospital District of Yogyakarta. This type of research is correlational with cross sectional design. The population in this study postpartum mothers in Sleman hospitals Yogyakarta with a sample of 67 respondents. The sampling technique that is accidental sampling. This research instrument in the form of questionnaires. Multivariate data analysis with multiple linear regression analysis. The results showed that the majority of respondents to behave fairly in terms of perineal wound care in the postpartum mother (mean 18.37). Sebagain respondents aged 20-23 years (73.14%). The majority of respondents with parity 1-2. The results of the bivariate analysis showed that there is a relationship between age and behavior of perineal wound care (p=0.000, r=0.549), there is a relationship between parity with perineal wound care (p=0.000, r=0.535). Multivariate analysis with multiple linear regression showed that between age and parity significantly associated with perineal wound care in the postpartum mother, but the t test results showed that the dominant age relates to the behavior of perineal wound care. Conclusion, there is relationship between age and parity with the behavior of perineal wound care postpartum mother at Sleman hospitals Yogyakarta. The age more dominant associated with behavior perineal wound care in postpartum mothers.